2016
DOI: 10.1080/00480169.2016.1171173
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of humeral fractures in a sample of dairy heifers

Abstract: The CT and histological findings were consistent with a diagnosis of osteoporosis. We propose that humeral fractures in dairy heifers are associated with osteoporosis, possibly as a result of insufficient deposition of bone during growth because of protein-calorie malnutrition. Increased osteoclastic resorption of bone associated with calcium mobilisation for lactation, and periods of copper deficiency may contribute to bone weakening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…Steers with low LW do not necessarily have low bone volume fraction. This agreed with the observation that a high humerus fracture in dairy heifers in New Zealand was associated with high osteoporosis induced by protein and energy malnutrition during the growing period (Dittmer et al 2016).…”
Section: Trabecular Bone Remodellingsupporting
confidence: 91%
“…Steers with low LW do not necessarily have low bone volume fraction. This agreed with the observation that a high humerus fracture in dairy heifers in New Zealand was associated with high osteoporosis induced by protein and energy malnutrition during the growing period (Dittmer et al 2016).…”
Section: Trabecular Bone Remodellingsupporting
confidence: 91%
“…However, the effect of growth and environment on subsequent bone development in dairy heifers has often been overlooked. Humeral fractures in first lactation dairy heifers were first reported in 2008 and represent a significant economic and welfare issue for the New Zealand dairy industry, with an estimated within-herd incidence of 4-25%, and approximately 5000 dairy replacements each year may be affected [3]. A case-control study of humeral fractures showed a reduction in cortical thickness and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study of humeral fractures showed a reduction in cortical thickness and osteoporosis. While the risk factors for humeral fracture are multifactorial, a major contributor is believed to be poor nutrition early in a heifer's life [3]. However, there is currently no published literature to inform on the timing and severity of nutrition restriction required to have an effect.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, spontaneous humeral fractures in first-lactation dairy heifers are reported to originate from the distal metaphysis [2]. Post-mortem examinations of spontaneous humeral fractures have shown an association with lower cortical bone thickness in affected bones, contributing to a decrease in bone strength (measured by stress-strain index) [2]. Growth arrest lines have also been observed in the humeri from heifers with spontaneous humeral fractures, indicating a period of malnutrition at some point in the heifer's life [2].…”
Section: Introductionmentioning
confidence: 92%
“…In cattle with normal cortical bone thickness, humeral fractures are rare (5% of all fractures in cattle and 18% of all long bone fractures) due to the protection provided by the biceps brachii, brachiocephalicus, and brachialis muscles that surround the humerus caudally, laterally and cranially [1]. In contrast, spontaneous humeral fractures in first-lactation dairy heifers are reported to originate from the distal metaphysis [2]. Post-mortem examinations of spontaneous humeral fractures have shown an association with lower cortical bone thickness in affected bones, contributing to a decrease in bone strength (measured by stress-strain index) [2].…”
Section: Introductionmentioning
confidence: 99%